Increased efficiency of accelerated testing of component parts of onboard equipment - Ленков, С. В.; Зубарев, В. В.; Маленко, В. І.; Салімов, Р. М.; Шомін, С. А. (Proceedings of National Aviation University (archive), 2002)
The method of shortening the time of conducting of accelerated tests of components of products of onboard equipment is considered, which allows to save money on their carrying out and to save the resource of test objects, provided that adequate detection of hidden defects is detected.